Prenatal Gentle Yoga Teknik Savasana Berpengaruh Terhadap Kecemasan Ibu Hamil Trimester III - Arliani, Dessie; Indriati, Ina; Aksohini, Tut Rayani (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
The pregnancy journey often brings about anxiety or stress due to significant transitions in a woman's life. Managing this anxiety involves both pharmacological and non-pharmacological approaches. One non-pharmacological method to alleviate anxiety in pregnant women during the third trimester is the Prenatal Gentle Yoga Savasana Technique. This study aimed to analyze the impact of Prenatal Gentle Yoga Savasana Technique on anxiety among third-trimester pregnant women in the Rejoso Community Health Center area in Pasuruan Regency. The research used a one-group pretest-posttest design approach. The population comprised all third-trimester pregnant women in the Rejoso Community Health Center area, totaling 15 pregnant women. The sample was selected using total sampling. Research instruments included a Standard Operating Procedure (SOP) for the independent variable and a questionnaire for the dependent variable. Data were analyzed using the Independent Sample t-test. The analysis results showed a p-value 0.05, indicating that the Prenatal Gentle Yoga Savasana Technique had an impact on anxiety among third-trimester pregnant women in the Rejoso Community Health Center area in Pasuruan Regency. The conclusion drawn from the research is that engaging in physical activity through prenatal yoga can reduce anxiety in pregnant women. Future research might delve deeper into the causes of anxiety and the unpreparedness of pregnant women in facing the childbirth process. Additionally, exploring other interventions to reduce anxiety in pregnant women and enhancing their knowledge in preparing for childbirth could be valuable areas for further study.